PENGARUH TEMPERATUR KONDENSOR TERHADAP KINERJA LEMARI PENDINGIN - agus dwi korawan (LPPM Politeknik LP3I Medan, 2020)
Household refrigerator is the need of every household to preserve food or other ingredients, as a consequence it requires a lot of electrical energy, whereas energy efficiency needs to be done, therefore research is needed to improve the performance of household refrigerators. So in this study conducted by varying the temperature of the condenser which aims to increase COP. The measured variables are the temperature of the refrigerant before the compressor, the temperature of the refrigerant after the compressor, the temperature of the refrigerant before the evaporator. In addition to knowing the cooling effect, the temperature of the cooling load is also measured in the evaporator. The study was conducted for 240 minutes. The results show that there is a difference in the temperature of the cooling load and also a difference in COP. Where the smaller the temperature of the condenser, the greater the COP.